Debating Holy Remains: a Discourse on Islamic Relics between the Sufi and Salafi Scholars - Gambari, Yusuph Dauda (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
Relics of holy people have been attractive among Muslims of all generations due to their mundane and spiritual importance. Sufi scholars are, especially, notable for their particular interest in relics, which form an integral part of their beliefs and practices. They venerate relics through which they seek blessing (tabāruk) and intercession (tawāṣul), among others. Meanwhile, the modern Salafi scholars criticized the Sufis’ perspective on relics, claiming that their actions constitute bid’ah (innovation), kufr (infidelity), and syirk (associating partners with Allah). This paper, therefore, examined the modern Salafis’ criticism of the religious attitudes of the Sufis on relics. It adopted both historical and exegetical methods to achieve the set objectives. It has been discovered that relics have spiritual values, and Muslims of all generations, especially the companions (ṣahābah), have used them for different spiritual purposes. It is also clear that both the Salafis and Sufis venerate and seek blessing from the relics, though Sufis are more prominent in the practice. The paper identified excessiveness and arbitrariness in the disposition of the Sufis to the relics, which engendered deification of them as the yardstick for the Salafis’ criticisms. Therefore, it concluded that advocacy for the desecration of relics on the part of modern Salafi scholars lacks merits. Instead, machinery to checkmate arbitrariness should be advocated for.